1999
DOI: 10.1074/jbc.274.42.30228
|View full text |Cite
|
Sign up to set email alerts
|

At Physiological Expression Levels the Kidd Blood Group/Urea Transporter Protein Is Not a Water Channel

Abstract: The Kidd (JK) blood group locus encodes a urea transporter that is expressed on human red cells and on endothelial cells of the vasa recta in the kidney. Here, we report the identification in human erythroblasts of a novel cDNA, designated HUT11A, which encodes a protein identical to the previously reported erythroid HUT11 urea transporter, except for a Lys 44 3 Glu substitution and a Val-Gly dipeptide deletion after proline 227, which leads to a polypeptide of 389 residues versus 391 in HUT11. Genomic typing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
53
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 35 publications
4
53
1
Order By: Relevance
“…Their conclusions were based upon expression studies in Xenopus laevis oocytes combined with volumetric measurements of water uptake at 10°C and [ 14 C]urea uptake at 1mmoll -1 at 23°C. Sidoux-Walter et al (Sidoux-Walter et al, 1999) questioned the conclusion by Yang and Verkman (Yang and Verkman, 1998). They showed that expression at high levels of the human RBC UT-B in Xenopus laevis oocytes induced not only high P urea and P f as reported by Yang and Verkman (Yang and Verkman, 1998), but also an increased permeability to small solutes, such as formamide through propionamide, and to diols, such as ethylene glycol and propylene glycol.…”
Section: Do Urea and Water Share A Pathway In Common In Rbc?mentioning
confidence: 69%
See 1 more Smart Citation
“…Their conclusions were based upon expression studies in Xenopus laevis oocytes combined with volumetric measurements of water uptake at 10°C and [ 14 C]urea uptake at 1mmoll -1 at 23°C. Sidoux-Walter et al (Sidoux-Walter et al, 1999) questioned the conclusion by Yang and Verkman (Yang and Verkman, 1998). They showed that expression at high levels of the human RBC UT-B in Xenopus laevis oocytes induced not only high P urea and P f as reported by Yang and Verkman (Yang and Verkman, 1998), but also an increased permeability to small solutes, such as formamide through propionamide, and to diols, such as ethylene glycol and propylene glycol.…”
Section: Do Urea and Water Share A Pathway In Common In Rbc?mentioning
confidence: 69%
“…The data indicate that the transport specificity disappeared at a high level of expression. In contrast, expression at physiological levels increased (as expected) the phloretin-sensitive urea transport with no increase of P f (Sidoux-Walter et al, 1999). A study by Lucien et al (Lucien et al, 2002) also pointed out that expression of a recombinant urea transporter (hUT-B1) in Xenopus oocytes creates a P urea that is efficiently inhibited by phloretin, but much less inhibited by PCMBS than the native P urea in human RBC.…”
Section: Do Urea and Water Share A Pathway In Common In Rbc?mentioning
confidence: 98%
“…It was reported that some AQP3 inhibitors suppressed the movement of water through AQP3 expressed in Xenopus oocytes but not the movement of glycerol and urea [19]. Moreover, it has been reported that the transport function of urea transporter 3, another water/cryoprotectant channel, differed depending on the level of its expression in the plasma membrane [20]. When urea transporter 3 was expressed in Xenopus oocytes at a physiological level, it transported only urea, but when it was overexpressed, it transported not only urea but also water and various small neutral solutes.…”
Section: Discussionmentioning
confidence: 99%
“…Whether urea transporters also transport water has been the subject of considerable interest (10,14,32,39). Early studies by Macey and Farmer (17) suggested that the erythrocyte urea transporter, which we now know to be UT-B, transports water.…”
Section: Discussionmentioning
confidence: 99%